Computer Technologies for Teaching and Self-directed Learning: Opportunities, Problems, and Coping Mechanisms - Elizabeth Lascano; Divina Yango (Diversitas Journal)
The demand in the use of computer technologies in education was amplified when pandemic struck the world.  Despite the opportunities derived from the use of these technologies, problems encountered can hamper the effectiveness of instruction and self-directed learning. With this, there is a need to look into the opportunities, problems, and coping strategies experienced by teachers and students.  Respondents include 69 faculty members and 414 college students enrolled in various degree programs in a State University in the Philippines. The study used descriptive survey and correlational research design.  The study reveals that both teachers and students highly use computer technologies (hardware/software) that benefited them.  Consequentially, both teachers and students acknowledged that computer technologies pose problems.  There is no significant correlation between the opportunities and problems for students, however, significant to highly significant correlations were noted for teachers.  Faculty and students use varied coping strategies in addressing problems encountered and is highly effective. Associated with this, there is a high extent of influence of factors in the coping strategies of respondents. Support from experts, availability and accessibility of technology resources as well as exposure to learning development activities are very essential support to faculty and students in effectively dealing with the challenges encountered.